2006
DOI: 10.1194/jlr.m600056-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet and metamorphosis upon the sterol composition of the butterfly Morpho peleides

Abstract: Whole body sterol metabolism in insects has seldom been studied. We were able to design an appropriate study at a butterfly farm in Belize. We collected six larvas of butterfly (Morpho peleides), their food (leaves of Pterocarpus bayessii), and their excretions. In addition, six adult butterflies were collected. The sterols of the diet, the larva, and adult butterfly were analyzed by gas-liquid chromatography. The structures of these sterols were identified by digitonin precipitation, GC-MS, and NMR. Four ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Overall, the lipid contents we report for B. mori are in the general range reported for a number of species of Lepidoptera (Domroese and Gilbert 1964;Fast 1964;Prasad et al 1986). Lipid and sterol concentrations are highly dependent on diet content and nutritional levels, even within species (Satake et al 2000;Connor et al 2006), so reported differences in the literature could be related, in part, to animal husbandry as well as to fundamental interor intraspecific differences. Lipid content differences in the cecropia moth are gender dependent (Domroese and Gilbert 1964), with females having higher lipid contents than males.…”
Section: Morphological and Biochemical Datamentioning
confidence: 97%
“…Overall, the lipid contents we report for B. mori are in the general range reported for a number of species of Lepidoptera (Domroese and Gilbert 1964;Fast 1964;Prasad et al 1986). Lipid and sterol concentrations are highly dependent on diet content and nutritional levels, even within species (Satake et al 2000;Connor et al 2006), so reported differences in the literature could be related, in part, to animal husbandry as well as to fundamental interor intraspecific differences. Lipid content differences in the cecropia moth are gender dependent (Domroese and Gilbert 1964), with females having higher lipid contents than males.…”
Section: Morphological and Biochemical Datamentioning
confidence: 97%
“…Total sterol content and the variation seems a function of species, diet, life stage and season (Connor et al, 2006;Koštál et al, 2013;Liland et al, 2017). While insects contain a variety of sterols often β-sitosterol, cholesterol, or 7-dehydrocholesterol are the most abundant (Cerda et al, 2001;Cheseto et al 2015;Connor et al, 2006;Jing and Behmer, 2020;Koštál et al, 2013;Liland et al, 2017;Mlček et al, 2019;Sabolová et al, 2016;Svoboda et al, 1995). High dietary levels of sterols, such as cholesterol, can increase the risk of atherosclerosis in humans and some species of monkeys (Hopkins, 1992;Rudel et al, 1998).…”
Section: Sterolsmentioning
confidence: 99%
“…The significant effect of larval diet on the concentration of pupal energetic loads (especially on lipid content) has been suggested (Nestel et al, 2004;Nishiura et al, 2006;Connor et al, 2006). On the other hand, in some cases larval diet composition does seem to affect neither carbohydrates nor protein levels (Slansky, 1985;Zanotto et al, 1993).…”
Section: Discussionmentioning
confidence: 96%